Air–water properties of unsteady breaking bores part 1: Novel Eulerian and Lagrangian velocity measurements using intrusive and non-intrusive techniques. (February 2023) - Shi, Rui; Wüthrich, Davide; Chanson, Hubert
Abstract: Transient motion, turbulence and bubble dynamics make any velocity quantification extremely difficult in unsteady gas–liquid flows. In the present study, novel Eulerian and Lagrangian techniques of velocimetry were developed, using both intrusive and non-intrusive measurements. The selected unsteady gas–liquid flow was a breaking bore, featured with a transient motion, air entrainment and coherent structures. Intrusively, Eulerian probe measurements resulted to the development of a single bubble event detection (SBED) technique in unsteady air–water flows. Non-intrusively, the motion of air–water pattern was detected using a novel particle tracking velocimetry (PTV). Both velocities obtained using SBED and PTV techniques were validated against the established optical flow (OF) results, achieving consistent velocity data among the three techniques. The filtering criteria of the SBED and PTV techniques were discussed, showing the best options in the breaking bore. It is concluded that the most robust velocity measurements in gas–liquid flow are achieved with consistent velocity data between the SBED, PTV and OF techniques. Graphical abstract: Highlights: Novel Eulerian and Lagrangian techniques were developed to obtain interfacial velocities in unsteady gas–liquid flows with high void fraction. A breaking bore was selected to test these techniques. For an Eulerian approach, single bubble event detection (SBED) technique was developed based on multiple phase-detection probes, providing the pseudo-instantaneous longitudinal velocity. For Lagrangian approach, the particle tracking velocimetry (PTV) was developed based on high-speed videos, providing particle trajectory and grid-averaged velocity contours.